Extracellular Vesicles Secreted by Mesenchymal Stromal Cells Exert Opposite Effects to Their Cells of Origin in Murine Sodium Dextran Sulfate-Induced Colitis - Tolomeo, Anna Maria; Castagliuolo, Ignazio; Piccoli, Martina; Grassi, Michele; Magarotto, Fabio; De Lazzari, Giada; Malvicini, Ricardo; Caicci, Federico; Franzin, Chiara; Scarpa, Melania; Macchi, Veronica; De Caro, Raffaele; et al. (Frontiers in Immunology, 2021)
Several reports have described a beneficial effect of Mesenchymal Stromal Cells (MSCs) and of their secreted extracellular vesicles (EVs) in mice with experimental colitis. However, the effects of the two treatments have not been thoroughly compared in this model. Here, we compared the effects of MSCs and of MSC-EV administration in mice with colitis induced by dextran sulfate sodium (DSS). Since cytokine conditioning was reported to enhance the immune modulatory activity of MSCs, the cells were kept either under standard culture conditions (naïve, nMSCs) or primed with a cocktail of pro-inflammatory cytokines, including IL1beta, IL6 and TNFalfa (induced, iMSCs). In our experimental conditions, nMSCs and iMSCs administration resulted in both clinical and histological worsening, and was associate with pro-inflammatory polarization of intestinal macrophages. However, mice treated with iEVs showed clinico-pathological improvement, decreased intestinal fibrosis and angiogenesis and a striking increase in intestinal expression of Mucin 5ac, suggesting improved epithelial function. Moreover, treatment with iEVs resulted in the polarization of intestinal macrophages towards and anti-inflammatory phenotype and in an increased Treg/Teff ratio at the level of the intestinal lymph node. Collectively, these data confirm that MSCs can behave either as anti- or as pro-inflammatory agents depending on the host environment. In contrast, EVs showed a beneficial effect, suggesting a more predictable behaviour, a safer therapeutic profile and a higher therapeutic efficacy with respect to their cells of origin.